Biopsychosocial determinant of quality of life of older adults in Pakistan and Canada - Batool, Syeda Shahida; Tanveer, Samra; Chatrath, Sarvjeet Kaur; Batool, Syeda Azra (Frontiers in Psychiatry, 2024)
Background The rapidly rising average age of the older adults has brought various global healthcare challenges. A core challenge is how to enhance their quality of life (QoL). Objective The objective of the current study was to test the significance of biopsychosocial determinants of quality of life of older adults in Pakistan and Canada. Methodology A cross-sectional survey was carried out on a conveniently approached purposive sample of 1,005 older adults (Pakistani = 557 and Canadian = 448) of age range between 60 years and 80 years. The data were collected via demographic datasheet, World Health Organization Quality of Life Brief Scale, Health and Lifestyle Questionnaire, General Self-Efficacy Scale, Rosenberg Self-Esteem Scale, and Berlin Social Support Scale. Results The results of hierarchical regression analysis showed that biopsychosocial factors (viz., health and lifestyle, chronic illness, self-efficacy, self-esteem, and social support) significantly predicted (R2 = .27, and.68) quality of life of older adults in Pakistan and Canada, respectively, after controlling the demographic variables. Significant differences were found between Pakistani and Canadian older adults on biopsychosocial factors: Canadian older adults scored significantly higher on health and lifestyle, self-efficacy, and quality of life, and older adults in Pakistan scored significantly higher on self-esteem and social support. Conclusion A significant amount of better QoL of older adults can be achieved through enhancing the biopsychosocial correlates of their QoL, both in Pakistan and Canada.